EVALUATION OF THE USE OF DIGITAL TECHNOLOGY AS A MEDIA FOR DISTRIBUTION OF PASSPORT SERVICE INFORMATION AT TPI PARE-PARE CLASS II IMMIGRATION OFFICE - A.Muh.Syaqil Aswad Syadzili (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
In implementing public services, the Class II Immigration Office of TPI Pare-Pare has used digital technology to convey immigration information, but there are several problems, namely there are still people who do not know about passport service information. The author seeks to evaluate the use of digital technology for the dissemination of passport service information at the Class II Immigration Office of TPI Pare-Pare. This study uses a descriptive research method with a qualitative approach. Data were collected by conducting interviews and observations and taking documents from the office. In data processing techniques used the model of Miles and Huberman. In disseminating information through digital media, the Class II Immigration Office of TPI Pare-Pare uses social media Instagram, Facebook and the Website. Information dissemination involves the use of Hardware, Software, and Brainware. Passport service information that is distributed via digital media at the Class II TPI Pare-Pare Immigration Office can be said to be of high quality because it meets the indicators of Relevancy, Acuracy, Timeliness, and Completeness. The obstacles experienced by the Class II TPI Pare-Pare Immigration Office in disseminating passport service information through digital technology are human errors such as errors in inputting letters causing typos in the disseminated information, technical errors, and environmental disturbances.